Evidence of Collaboration and Connectivity of Sulawesi Railway Operations - Hermansyah, Andi; Rasyid, Imran; Selvira, Rizka (Jurnal Global Ilmiah, 2025)
The development of railway infrastructure in Sulawesi aims to meet the needs of freight and passenger transportation, as well as to encourage regional economic growth. This study aims to analyze collaboration and connectivity in railway operations in Sulawesi, and evaluate the factors that influence the development of the railway network. The method employed is comparative descriptive analysis, utilizing the Government Collaboration model and NVivo tools to categorize the data. The results of the study show that the construction of the railway line reaches around 145 kilometers between Makassar and Parepare, with support from the central and regional governments and various stakeholders. In addition, the analysis shows that collaboration between stakeholders is important in realizing the success of this project. In conclusion, the development of the railway network in Sulawesi can improve mobility, accessibility, and efficiency of goods distribution, as well as contribute to sustainable economic growth. This study recommends the need for attention to technical planning and solving land acquisition problems for the sustainability of the project in the future.